Distribusi Spasial Suhu dan Salinitas di Perairan Selat Haruku - Simon Tubalawony; Degen Erasmus Kalay; Wiwien Gaby Hukubun; Ronald Darlly Hukubun (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The waters of the Haruku Strait have very fluctuating water mass movements caused by various oceanographic factors, making the water column very dynamic. This study aims to study and analyze the physical oceanographic characteristics of the waters in the form of temperature and salinity distribution. Research data was taken and recorded by CTD on each transect then tabulated and analyzed using Microsoft Excel, Surfer and Ocean Data View (ODV). The results of data analysis showed that the temperature value at the observation station, from sea surface to a depth of 25 meters, ranged from 28.71–29.6 oC, while at a depth of 50–100 meters, the temperature ranged from 24.68–28.11 oC. The distribution of salinity values ​​in sea surface waters to a depth of 25 m ranges from 33,12–33,60 psu while at a depth of 50–100 m the temperature ranges from 33,83–34,38 psu. The characteristics of the water mass are influenced by the mass of water from the Banda Sea and the Seram Sea, freshwater input from the mainland, and community activities on the coast. In general, the water column has a different temperature and salinity stratification for each depth. The temperature conditions will decrease, and the salinity value will increase with increasing depth.